Novel Antitumor and Radioprotective Sulfonamides Containing Pyrrolo[2,3-d]pyrimidines - Ghorab, Moustafa M.; Noaman, Eman; Ismail, Magda M. F.; Heiba, Helmy I.; Ammar, Yousry A.; Sayed, Marwa Y. (Arzneimittelforschung, 2006)
Several sulfonamides having pyrrole (5a-c, 8, 11b-19, 23, 24), pyrrolo[2,3-d] pyrimidine (6, 7, 10, 20, 21, 25) and pyrrolo[2,3-b]pyridine (22) were synthesized and evaluated for their antitumor and radioprotective activities. The structure of the synthesized compounds was elucidated by elemental analyses and spectral data. Compounds 5a, 16, 17, 19, and 23 displayed more potent antitumor activities than the reference drug, doxorubicin. On the other hand compounds 19, 23 and 25 exhibited radioprotective activities.
Keywords: Antitumor agents; Pyrrole derivatives, synthesis; Pyrrolo[2,3-d]pyrimidine derivatives, synthesis; Radioprotective agents